Problems of Insya' Tahriry Learning in Higher Education: A Case Study of Linguistic and Non-Linguistic Obstacles - Shofiyah Shofiyah; Anwar Sidik (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Mastering writing skills (maharah al-kitabah) through the Insya’ Tahriry course represents the pinnacle of language proficiency for Arabic Language Education students. However, a significant gap exists between expected competencies and students' actual abilities, leading to a stagnation in the quality of their scientific work. This study aims to identify linguistic and non-linguistic obstacles through a qualitative case study approach using descriptive content analysis. The primary data source consists of fourth-semester student assignment portfolios analyzed through error analysis procedures. Research findings indicate that dominant linguistic obstacles include syntactic errors (i’rab), morphological distortions in tashrif, and strong mother-tongue interference. Non-linguistically, barriers are triggered by writing anxiety, disparities in educational backgrounds, and a lack of clinical feedback, which leads to language fossilization. The study concludes that pedagogical transformation is required through collaborative manuscript "dissection" and the strengthening of a digital-based bi’ah lughawiyyah. This humanistic-clinical approach is expected to break the cycle of learning problems to produce competitive Arabic educators in the global era.